Genetic variability and interrelationships of grain yield and its components of irrigated rice in Gezira - Osman, Khalid A.; Mustafa, Ahmed M.; Ibrahim, Abu Elhassan S. (Gezira Journal of Agricultural Science; Vol 5 No 2 (2007), 2007)
Nineteen genotypes of irrigated rice were evaluated at the Gezira Research Station Farm, Wad Medani, Sudan, for two consecutive seasons (2004 and 2005) in a randomized complete block design with three replicates. This study was conducted to estimate the genotypic and phenotypic variability, broad sense heritability and traits correlation with grain yield. The highest genotypic coefficient of variation and genetic advance were recorded for plant height and number of panicles/m 2 , and the lowest for number of tillers/plant, days to 50% flowering, days to 50% maturity and panicle length, in both seasons. High heritability estimates (>80%) were recorded for plant height, days to 50% flowering, days to 50% maturity and 1000-grain weight. The highest estimate of heritability combined with the highest genetic advance as percentage of the mean was shown by plant height and 1000-grain weight, in both seasons. The high yielding genotypes were WITA5 (TOX 3255-82-1-3-2), IRI 3240-108-2-2-3(SAHEL.108)(FKR44) and TOX 3081-36-2-2-3-1. Their grain yields were 4.9, 4.9 and 4.6 t/ha, respectively. Grain yield/ha was significantly and negatively correlated with the percentage of unfilled grains/panicle, plant height and days to 50% flowering. How-ever, it was significantly and positively correlated with number of tillers/ plant, number of panicles/m 2 , number of filled grains/panicle and 1000-grain weight, in both seasons. Path coefficient analysis indicated that number of filled grains/panicle, 1000-grain weight and number of panicles / m 2 were the most directly related traits to grain yield/ha.